2013
DOI: 10.1371/journal.pone.0063605
|View full text |Cite|
|
Sign up to set email alerts
|

Identifying Optimal Vaccination Strategies for Serogroup A Neisseria meningitidis Conjugate Vaccine in the African Meningitis Belt

Abstract: ObjectiveThe optimal long-term vaccination strategies to provide population-level protection against serogroup A Neisseria meningitidis (MenA) are unknown. We developed an age-structured mathematical model of MenA transmission, colonization, and disease in the African meningitis belt, and used this model to explore the impact of various vaccination strategies.MethodsThe model stratifies the simulated population into groups based on age, infection status, and MenA antibody levels. We defined the model parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 35 publications
1
32
0
Order By: Relevance
“…One of the limitations of our study stems from the assumption that polyvalent vaccines offer the same degree of protection against all serogroups. This assumption is consistent with existing models that aggregate serogroups into "vaccine" and "non-vaccine" type [33,40,[47][48][49] and is also necessitated by the lack of data to characterize serogroup competition [40]. As polyvalent vaccines offer protection against all meningococcal serogroups, our model only describes the circulation of one 'vaccine' serogroup.…”
Section: Discussionsupporting
confidence: 68%
“…One of the limitations of our study stems from the assumption that polyvalent vaccines offer the same degree of protection against all serogroups. This assumption is consistent with existing models that aggregate serogroups into "vaccine" and "non-vaccine" type [33,40,[47][48][49] and is also necessitated by the lack of data to characterize serogroup competition [40]. As polyvalent vaccines offer protection against all meningococcal serogroups, our model only describes the circulation of one 'vaccine' serogroup.…”
Section: Discussionsupporting
confidence: 68%
“…A mathematical model developed to identify optimal long-term PsA-TT vaccination strategies using surveillance and carriage data from Burkina Faso demonstrated that either strategy, introduction into EPI or repeat mass campaigns, would be effective in substantially reducing MenA incidence over a 40 year period following the initial mass immunization campaign. The most effective modelled strategy is mass immunization campaigns in 1–5 year olds every 5 years, with introduction of PsA-TT into the routine EPI program resulting in higher predicted MenA incidence than periodic immunization campaigns [13]. However, there is limited data on the duration of protection following PsA-TT vaccination, and thus forecasts of vaccine program impact may vary depending on assumptions made about duration of protection.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy might be a better option in areas where EPI vaccination coverage is low. Tartof et al developed a mathematic model of serogroup A meningitis incidence in the meningitis belt and concluded that the most effective strategy was mass vaccination of 1-to 5-year-old children every 5 years, and that introducing the vaccine in EPI programs at 9 months of age was less effective [85]. Overall vaccination coverage in Burkina Faso after MenAfriVac mass vaccination was comparable to that attained for routine measles vaccination, but regions with suboptimal vaccination coverage for measles might also be at risk for coverage below targets if MenAfriVac is introduced in EPI [69].…”
Section: Future Steps For Menafrivac -Protecting New Birth Cohortsmentioning
confidence: 99%